2017
DOI: 10.1002/pc.24606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basalt fiber hybridization on the vibration‐damping behavior of carbon fiber/epoxy composites

Abstract: Carbon fiber reinforced polymer composites (CFRPs) have increasingly gained importance among the scientific community as well as industry due to their high specific strength and light weight properties. However, CFRPs suffer from menace of high frequency vibration and low damping ability under normal operating conditions. This study aimed to experimentally investigate the effect of basalt fiber hybridization on vibration damping and tensile properties of carbon fiber/epoxy composites. Interply hybrid composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…Furthermore, only a few studies devoted to free vibration characteristics of basalt or carbon fiber reinforced composites are seen in the literature. Bozkurt and Gökdemir (2018) examined the influences of basalt hybridization on the tensile and dynamic characteristics of carbon fiber reinforced composite laminates. It was demonstrated that the inclusion of basalt fiber resulted with an enhancement in damping properties and decrease in tensile characteristics of carbon fiber reinforced composite laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only a few studies devoted to free vibration characteristics of basalt or carbon fiber reinforced composites are seen in the literature. Bozkurt and Gökdemir (2018) examined the influences of basalt hybridization on the tensile and dynamic characteristics of carbon fiber reinforced composite laminates. It was demonstrated that the inclusion of basalt fiber resulted with an enhancement in damping properties and decrease in tensile characteristics of carbon fiber reinforced composite laminates.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the flexural properties strongly depended on the reinforcing position of carbon and basalt fabric [10]. Bozkurt et al [11] experimentally investigated the effect of basalt fiber hybridization on vibration damping and tensile properties of carbon fiber/epoxy composites prepared using VARTM process. The results showed that incorporation of basalt fiber into the carbon fiber/epoxy composites significantly affected the tensile strength, tensile modulus and enhanced damping properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bozkurt et al [11] experimentally investigated the effect of basalt fiber hybridization on vibration damping and tensile properties of carbon fiber/epoxy composites prepared using VARTM process. The results showed that incorporation of basalt fiber into the carbon fiber/epoxy composites significantly affected the tensile strength, tensile modulus and enhanced damping properties [11]. Fiore et al [12] evaluated the influence of external layers of basalt on the durability behaviour of flax reinforced epoxy composites prepared using vacuum bagging method (VBM).…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Bozkurt and Gökdemir, 12 effects of using basalt fiber layers in between the epoxy/CF composite laminates was investigated. They indicated that although use of basalt fiber layers decreased the tensile strength and tensile modulus of the epoxy/CF composite laminates; increasing the basalt fiber layers increased the damping ratio of the laminates up to 61%.…”
Section: Introductionmentioning
confidence: 99%